Targeting TNFR2 in Cancer: All Roads Lead to Rome - Bai, Jingchao; Ding, Bowen; Li, Hui (Frontiers in Immunology, 2022)
TNF receptor 2 (TNFR2) has become the most potential immune checkpoints might be targeted mainly because of its vital role in tumor microenvironments (TME). Overexpression of TNFR2 in some tumor cells and essential function in immunosuppressive cells, especially Treg cells, make blocking TNFR2 an excellent strategy in cancer treatment, however, there are other evidences showing that activating TNFR2 can also inhibit tumor progression in vivo. In this review, we will discuss drugs blocking and activating TNFR2 under clinical trials or preclinical developments up till now, meanwhile, summarize and explore the possible mechanisms related to them.